Substantiaton of selecting the method of pre-cooling of fruits - Serdyuk, Marina; Stepanenko, Dmitrij; Baiberova, Svitlana; Gaprindashvili, Nonna; Kulik, Alina (Eastern-European Journal of Enterprise Technologies, 2016)
The research is devoted to the scientific substantiation of the feasibility of combination of precooling the fruits and their treatment by antioxidant compositions before prolonged storage, as well as determining the optimal modes and methods of carrying out the given technological operation. The objects of research were the fruits of apple varieties Aydared, Golden Delicious, Simirenko Renet, Florin, the fruits of pear varieties Izyuminka Crimea and Conference, the fruits of plum varieties Voloshka and Stenley. Precooling was conducted in three ways: by cold air in conventional storing chambers, by cold air in the chambers of intensive cooling and hydrocooling in the solutions of antioxidant compositions. As a result of the studies, it was found that the most intensive method of precooling is cooling by air at temperature minus 2…minus 4 oC and airflow velocity 3 m/s. Under such circumstances, general period of cooling to a temperature 0 oC of the apple fruits and pear fruits is about 2 hours and the plum fruits – slightly longer than 1 hour. The velocity constant of reduction in the intensity of breathing and heat release of fruits during intensive cooling exceeded the velocity constant of the analyzed indices during slow cooling by 4.3…6.6 times and during hydrocooling by 1.2...1.6 depending on the type of fruit. Along with this, high speed of air motion increased the natural weight loss of fruits during cooling. The quantitative value of this indicator during intensive method was maximum and varied in the range of 0.56 % for the pear fruits to 0.44 % for the plum fruits. Combined method, which implies initial precooling in the working solutions of antioxidant compositions and further cooling by the intensive method, was characterized by high velocity constant of reduction in the intensity of breathing and heat release of the fruits and low level of the natural loss weight. In this case, the quantitative value of the weight loss varied in the range from 0.005 % for plum fruits to 0.014 % for the apple and pear fruits.